Assessment of the safety of Roxadustat for cardiovascular events in chronic kidney disease-related anemia using meta-analysis and bioinformatics - Li, Xiangmeng; Jiang, Shimin; Gu, Xia; Liu, Xiaojing; Shang, Shunlai; Zhang, Jiao; Pang, Keying; Li, Wenge (Frontiers in Pharmacology, 2024)
Objective: This study compares the cardiovascular risk in anemic chronic kidney disease patients treated with Roxadustat versus erythropoietin stimulating agents (ESAs). It also explores the cardiovascular impact of Roxadustat. Methods: We searched PubMed, EMBASE, Cochrane, Scopus, and Web of Science databases up to August 13, 2023, using terms such as "ESA," "Roxadustat," "MACE," "stroke," "death," "myocardial infarction," and "heart failure." Data were sourced from the NCBI database by filtering for "Roxadustat" and "human," and differentially expressed genes were identified using R software, followed by GO enrichment analysis, KEGG pathway analysis, and protein interaction network analysis. Results A total of 15 articles encompassing 143,065 patients were analyzed, including 138,739 patients treated with ESA and 4,326 patients treated with Roxadustat. In the overall population meta-analysis, the incidences of Major Adverse Cardiovascular Events (MACE), death, and heart failure (HF) were 13%, 8%, and 4% in the Roxadustat group, compared to 17%, 12%, and 6% in the ESA group, respectively, with P-values greater than 0.05. In the subgroup analysis, the incidences were 13%, 11%, and 4% for the Roxadustat group versus 17%, 15%, and 5% for the ESA group, also with P-values greater than 0.05. Bioinformatics analysis identified 59 differentially expressed genes, mainly involved in the inflammatory response. GO enrichment analysis revealed that these genes are primarily related to integrin binding. The main pathways identified were the TNF signaling pathway, NF-κB signaling pathway, and lipid metabolism related to atherosclerosis.      The protein interaction network highlighted IL1B, CXCL8, ICAM1, CCL2, and CCL5 as the top five significantly different genes, all involved in the inflammatory response and downregulated by Roxadustat, suggesting a potential role in reducing inflammation.      Conclusion The meta-analysis suggests that the use of Roxadustat and ESA in treating anemia associated with chronic kidney disease does not significantly alter the likelihood of cardiovascular events in the overall and American populations. However, Roxadustat exhibited a safer profile with respect to MACE, death, and HF.      The bioinformatics findings suggest that Roxadustat may influence integrin adhesion and affect the TNF and NF-κB signaling pathways, along with lipid and atherosclerosis pathways, potentially reducing inflammation.